2020
DOI: 10.1080/02656736.2020.1753828
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of the thermal effects of irreversible electroporation for in vitro, in vivo, and clinical use: a systematic review

Abstract: Introduction: Irreversible electroporation (IRE) is a relatively new ablation method for the treatment of unresectable cancers. Although the main mechanism of IRE is electric permeabilization of cell membranes, the question is to what extent thermal effects of IRE contribute to tissue ablation. Aim: This systematic review reviews the mathematical models used to numerically simulate the heatgenerating effects of IRE, and uses the obtained data to assess the degree of mild-hyperthermic (temperatures between 40 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 95 publications
(352 reference statements)
4
42
1
Order By: Relevance
“…Therefore, a higher number of pulses are needed to exert such action, which results in longer treatments [ 18 ]. Additionally, due to the higher number of pulses, IRE contains a nonnegligible thermal component, which can introduce additional safety concerns when treating targets near temperature-sensitive tissue, such as the central bile ducts [ 15 , 22 , 23 , 24 ]. In contrast, the advantage of ECT is the utilization of a smaller number of pulses for reversible electroporation of cells and the induction of apoptotic cell death with delayed action of cytotoxic agents and not electric pulses [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a higher number of pulses are needed to exert such action, which results in longer treatments [ 18 ]. Additionally, due to the higher number of pulses, IRE contains a nonnegligible thermal component, which can introduce additional safety concerns when treating targets near temperature-sensitive tissue, such as the central bile ducts [ 15 , 22 , 23 , 24 ]. In contrast, the advantage of ECT is the utilization of a smaller number of pulses for reversible electroporation of cells and the induction of apoptotic cell death with delayed action of cytotoxic agents and not electric pulses [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The irreversible aspect is a result of the number of pores created such that a cell cannot recover from the collapse of cell membrane function. Though presented as non-thermal, inclusion of IRE in this review is justified since significant temperature rises in the hyperthermic and in the thermal ablation range are reported to occur during IRE, significantly contributing to the ablation effect [284][285][286][287][288][289][290]. These significant temperature increases are a result of the excessively high SAR generated in a short time (1 -10 min) in the treatment area during IRE, particularly close to the electrodes.…”
Section: Electroporationmentioning
confidence: 99%
“…In IRE ablation, the cell death is predominantly a result of electroporation and not the temperature increase. However, local heating of tissue does occur, especially in the immediate vicinity of the electrodes and when large numbers of pulses are used [12,14,15]. IRE ablation has been used in clinical trials for treatment of tumors in internal organs such as liver, pancreas, kidneys and prostate [11,[16][17][18][19].…”
Section: Ire Ablation Therapymentioning
confidence: 99%
“…IRE ablation is usually considered a non-thermal method. However, several experimental in vivo and in silico studies have shown a significant increase in temperature during treatment [ 14 , 15 , 20 , 29 , 30 ]. Thermal coagulation has been observed a few millimeters from the electrodes in animal experimental studies [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%